Establishing remote networks for ROS applications via Port Forwarding: A detailed tutorial - Hajjaj S.S.H.; Sahari K.S.M. (SAGE Publications Inc., 2023)
Agricultural robots; Application programs; Computer software; Middleware; Wi-Fi; Cloud robotics; Indoor robots; Networked components; Port forwarding; Remote networks; Robot operating systems (ROS); Robot performance; Wi-Fi hotspot; Robots